Penerapan Model Pembelajaran STAD dan Metode Demonstrasi dalam Matakuliah Pengetahuan Lingkungan pada Mahasiswa Pendidikan Biologi - Erman Har (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The focus of this study is to describe the difference of students' learning outcomes, in the subjec,t of environmental knowledge Between the application of STAD learning model with the application of demonstration, learning method. This experimental study was conducted on even semesters 2015/2016 and even semester 2016/2017. The research instrument uses test questions even semester 2015/2016 and even semester 2016/2017. Data analysis looks at the reliability and validity of the questions and test the difference , in learning outcomes, with t-tests. Additional instruments used as a tool for collecting research data is an interview with 5 students in every semester even. The results showed, that there were significant, differences (α = 0.05). The result of learning environmental knowledge between the application of STAD learning model with the application of demonstration learning method (Sig =0.043≤ α=0.05) STAD (78.3) whereas the mean learning outcomes of the demonstration learning method (83.2). Demonstration learning methods show higher learning outcomes compared to the STAD learning model. Based on interviews conducted on the students provide information that the demonstration method is more challenging and realistic and can be practiced directly about the material being studied. When the formation of small groups is an advantage of STAD type cooperative learning model. The implication that can be given in this research is demonstration learning methods in the learning of environmental knowledge, can be applied, by the teaching staff as one method that can provide good learning outcomes.